Positive electrode material, positive plate thereof and secondary battery
By introducing 0.5nm to 30nm microcracks into the cathode material and controlling their number to account for 1.5% to 13% of the total number of particles, the problem of gas production in the cathode material under high voltage is solved and the stability and safety of the material are improved. and specific capacity.
Patent Information
- Application Number
- CN202411940321.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
AI Technical Summary
The existing cathode materials have gas production problems due to structural instability at high voltages, which affects the stability and safety of the materials.
By introducing micro -cracks from 0.5nm to 30nm in the positive material, the number of microcracreta controls the number of microcracions accounted for 1.5%to 13%of the total number of particles to reduce the continuous infiltration of electrolytes on the pelvic particles of the positive pole material, thereby reducing the production of gas production.
Effectively reduce the gas production behavior of the positive pole material in the secondary battery, improve the cycle stability and safety, and increase the active area, thereby increasing the battery ratio.
Smart Images

Figure CN119361684A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] In the conventional preparation process, the positive electrode material precursor is mixed and sintered to grow into nuclei, and then dispersed and crushed to form a powder. The crushed material is then coated and post-treated to make the positive electrode material. However, the positive electrode material obtained by such conventional positive electrode material preparation methods has insufficient structural stability, and the conventional coating post-treatment cannot solve the problem of structural stability being destroyed during the sintering and dispersion stages. Under high voltage, there will be gas production problems due to the destruction of the structure during the dispersion process, affecting the stability and safety of the positive electrode material. Summary of the invention
[0003] In view of this, the present application provides a positive electrode sheet to solve at least one of the above problems.
[0004] To achieve the above-mentioned purpose, the present application provides a positive electrode material, the positive electrode material includes a plurality of particles, at least some of the particles have microcracks, the size of the microcracks is 0.5nm to 30nm, and the number of particles with microcracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material. The testing method of the number proportion includes: performing a scanning electron microscope test on the positive electrode material to obtain a scanning electron microscope image, selecting 300 positive electrode material particles in the scanning electron microscope image, counting the number of positive electrode material particles with microcracks, and obtaining the number proportion.
[0005] In some possible implementations, the number of particles with microcracks accounts for 4% to 8% of the total number of particles of the positive electrode material.
[0006] In some possible implementations, the microcracks are located on the surface of the particle and extend toward the interior of the particle, or are located inside the particle and communicate with the surface of the particle.
[0007] In some possible implementations, the gas production of the cathode material at 60° C. over 7 days is 0.1 mL / g to 1 mL / g.
[0008] In some possible implementations, the strain rate of the positive electrode material is 0.035% to 0.13%.
[0009] In some possible implementations, the positive electrode material is a single crystal positive electrode material.
[0010] In some possible implementations, the particle includes one or more primary particles, all primary particles in at least one particle have the same orientation, and the average particle size of the primary particles is 1 µm to 5 µm.
[0011] In some possible implementations, the specific surface area of the cathode material is 0.5 m 2 / g to 1 m 2 / g.
[0012] In some possible implementations, the particle sizes D10, D50 and D90 of the positive electrode material satisfy (D90-D10) / D50 greater than or equal to 1.0.
[0013] In some possible implementations, the tap density of the positive electrode material is greater than or equal to 1.8 g / cm 3 .
[0014] In some possible implementations, the powder compaction density of the cathode material at 3 T tonnage is greater than or equal to 3.0 g / cm 3 .
[0015] In some possible implementations, the powder conductivity of the positive electrode material is greater than or equal to 1×10 -4 S / cm.
[0016] In some possible implementations, the unit cell size of the positive electrode material is 80 nm to 110 nm.
[0017] In some possible implementations, the general formula of the positive electrode material is Li a Ni b Co c M (1-b-c) O2, wherein 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, b+c≤1, and M includes one or more of Mn, Ti, Zr, Ca, W, Ba, Y, Nb, Mo, La, Sr, and B.
[0018] In some possible implementations, the positive electrode material includes a core and a coating layer, wherein the coating layer is disposed on at least a portion of the surface of the core, and the coating layer includes Li x N y O2, wherein 0≤x≤5, and N is one or more of Zr, Ti, Al, W, Nb, La, Mo and Y.
[0019] The present application also provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode material above.
[0020] The present application also provides a secondary battery, comprising the above-mentioned positive electrode sheet.
[0021] In the positive electrode material of the present application, based on the total number of positive electrode material particles, when the number of positive electrode material particles with microcracks accounts for 1.5% to 13%, the continuous infiltration of the electrolyte into the positive electrode material particles can be effectively reduced, thereby being able to more effectively reduce the gas production behavior of the positive electrode material in the secondary battery, which is beneficial to improving the cycle stability and safety of the secondary battery, so that the electrode sheet based on such positive electrode material maintains a high degree of compaction, the distance between the positive electrode material particles is reduced, the contact area is increased, the conductive channels and bridges are increased, and the active area that can participate in the reaction is increased, which is beneficial to improving the specific capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the structure of microcracks in the positive electrode material particles provided in this application.
[0023] Figure 2 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during charging.
[0024] Figure 3 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present application during discharge.
[0025] Figure 4 This is a SEM image of the positive electrode material provided in Example 1 of the present application before rolling.
[0026] Figure 5 This is a SEM image of the positive electrode material provided in Example 1 of the present application after rolling.
[0027] Figure 6 This is a SEM image of the positive electrode material provided in Example 1 of the present application after charge and discharge cycles.
[0028] Figure 7 This is a SEM image of the positive electrode material provided in Example 2 of the present application before rolling.
[0029] Figure 8 This is a SEM image of the positive electrode material provided in Example 2 of the present application after rolling.
[0030] Fig. 9 This is a SEM image of the positive electrode material provided in Example 2 of the present application after charge and discharge cycles.
[0031] Fig.10 This is a SEM image of the positive electrode material provided in Comparative Example 1 of the present application before rolling.
[0032] Fig.11 This is a SEM image of the positive electrode material provided in Comparative Example 1 of the present application after rolling.
[0033] Fig.12This is a SEM image of the positive electrode material provided in Comparative Example 1 of the present application after charge and discharge cycles.
[0034] Fig.13 This is a SEM image of the positive electrode material provided in Comparative Example 4 of the present application before rolling.
[0035] Fig.14 This is a SEM image of the positive electrode material provided in Comparative Example 4 of the present application after rolling.
[0036] Fig.15 This is a SEM image of the positive electrode material provided in Comparative Example 4 of the present application after charge and discharge cycles.
[0037] Main component symbols Positive electrode material particles 10 Cracks 11, 12, 13 Electrode assembly 100 Positive electrode 101 Negative electrode 102 Isolation film 103. DETAILED DESCRIPTION
[0038] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0039] After the positive electrode material is sintered and grown into nuclei, it is rolled to form a powder. It is generally believed that the powder is the source of gas production of the positive electrode material. In response to the gas production problem of the positive electrode material under high voltage, the related art maintains the interface stability of the positive electrode material by surface treatment of the positive electrode material, such as coating treatment, to improve the gas production problem of the positive electrode material under high voltage environment. However, the surface coating generally forms an island coating, which is difficult to form uniform protection. It cannot effectively improve the gas production problem, and too much coating material will also affect the capacity of the positive electrode material and increase the manufacturing cost. In the related art, the gas production behavior of the material is also reduced by increasing the strength of the positive electrode material and reducing the micropowder produced by rolling. However, improving the generation of micropowder can only reduce the initial gas production of the positive electrode material, and still cannot effectively solve the gas production problem of the positive electrode material under long-term high temperature conditions. Moreover, this method will reduce the compaction of the material's pole piece, and also put forward stringent requirements on the material's crushing and sintering process, which is not conducive to the commercial application of the material.
[0040] Through research, this application found that the gas generation behavior of the positive electrode material is affected by the content of microcracks in the positive electrode material particles. Figure 1 There are three main sources of microcracks in the positive electrode material particles 10. One is the cracks 11 generated during the growth of the positive electrode material particles 10 due to the anisotropy of the unit cell. One is the cracks 12 generated during the crushing or rolling of the positive electrode material particles 10. The other is the intercrystalline displacement generated after the positive electrode material particles 10 participate in the charge and discharge cycle until the cracks 13 are generated. The above cracks 11 and 12 will cause the electrolyte to continuously erode from the outside of the material to the inside of the positive electrode material particles 10. In practical applications, the electrolyte will continue to infiltrate the positive electrode material particles 10, resulting in a large number of side reactions, causing difficult-to-control gas production deterioration and other adverse effects. In addition, microcracks are intrinsic defects of positive electrode material particles. Simply improving the mechanical strength of positive electrode material particles or controlling the generation of micropowders cannot avoid the generation of microcracks, nor can it avoid the problem of continuous gas production caused by microcracks.
[0041] In view of the gas generation mechanism of the positive electrode material under high pressure discovered by the inventor of the present application, one embodiment of the present application provides a secondary battery, including a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0042] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, the secondary battery is a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0043] See also Figure 2 and Figure 3 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103. The separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. When an electrolyte (not shown) is provided, when charging, refer to Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 3 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material, generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances.
[0044] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0045] Positive electrode The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer, wherein the positive electrode material active layer includes a positive electrode material, a binder and a conductive agent. The positive electrode material, the binder and the conductive agent are made into a slurry, and the slurry is coated and rolled onto the positive electrode current collector to form a positive electrode sheet.
[0046] The positive electrode current collector can be a composite current collector. For example, the metal foil can use aluminum foil or nickel foil. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.
[0047] The positive electrode material layer includes a positive electrode material, which includes a plurality of particles, at least some of which have microcracks, the size of the microcracks is 0.5nm to 30nm, and the number of particles with microcracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material. A testing method for the number ratio includes: performing a scanning electron microscope test on the positive electrode material to obtain a scanning electron microscope image, selecting 300 positive electrode material particles in the scanning electron microscope image, counting the number of positive electrode material particles with microcracks, and obtaining the number ratio.
[0048] It should be noted that, in the present application, the above-mentioned positive electrode material includes the positive electrode material in a powder state, and the positive electrode material in the positive electrode sheet after the positive electrode sheet is made.
[0049] The applicant found that when the microcracks of the positive electrode material particles in the present application are less than 0.5 nm, the microcrack size is too small, which is not conducive to electrolyte infiltration, and the negative impact on the physical indicators and chemical properties of the positive electrode material particles themselves and in the subsequent battery application process can be ignored. When the cracks are larger than 30 nm, the oversized cracks may have caused the positive electrode material particles to break or break, and the number of positive electrode material particles with such oversized sizes is small. Therefore, the applicant believes that it no longer falls within the scope of microcracks in the present application. Therefore, the present application further studies the presence of microcrack particles of 0.5nm to 30nm in the positive electrode material particles, and the microcracks are mainly generated by unit cell anisotropy or a crushing process, and finds that based on the total number of positive electrode material particles, when the number of positive electrode material particles with the above-mentioned microcracks accounts for 1.5% to 13%, it can effectively reduce the continuous infiltration of the electrolyte into the positive electrode material particles, thereby effectively reducing the gas production behavior of the positive electrode material in the secondary battery, which is beneficial to improving the cycle stability and safety of the secondary battery, and can also control the intercrystalline displacement generated by the positive electrode material particles after participating in the charge and discharge cycle in actual applications until the cracks are generated; at the same time, it can also enable the positive electrode sheet based on the above-mentioned positive electrode material to maintain a high compaction density, increase the contact area between the positive electrode material particles, increase the conductive channels and bridges, and increase the active area that can participate in the reaction, which is beneficial to improving the specific capacity of the secondary battery. When the proportion of positive electrode material particles with the above-mentioned microcracks in the total number of positive electrode material particles is too low (i.e., less than 1.5%), the positive electrode material particles are too round, which will lead to low compaction density of such material powders, and then low compaction density of positive electrode sheets, affecting electronic conductivity and specific capacity of secondary batteries. When the proportion of positive electrode material particles with the above-mentioned microcracks in the total number of positive electrode material particles is too high (i.e., higher than 13%), after such positive electrode materials are made into secondary batteries, the gas production of the secondary batteries will be significantly deteriorated and more difficult to control.
[0050] In some embodiments, the number of particles with microcracks accounts for 4% to 8% of the total number of particles of the positive electrode material. Based on the total number of particles of the positive electrode material, when the number of particles of the positive electrode material with the above-mentioned microcracks is further controlled to account for 4% to 8%, the gas generation behavior of the positive electrode material when used as a secondary battery can be further reduced, especially the probability of intercrystalline displacement and cracks generated after the positive electrode material participates in the charge and discharge cycle can be reduced, and at the same time, the pole piece based on the positive electrode material has a higher compaction density, which is beneficial to the stability, safety and specific capacity of the secondary battery.
[0051] In some embodiments, the microcracks are provided on the surface of the particles and extend toward the interior of the particles, or are provided inside the particles and connected to the surface of the particles. The above-mentioned microcracks will cause the electrolyte to continuously erode from the outside of the material to the inside of the positive electrode material particles, and in practical applications, will continuously aggravate the infiltration of the electrolyte into the positive electrode material particles, thereby causing a large number of side reactions, resulting in difficult-to-control gas production deterioration and other adverse effects. It should be noted that if there are microcracks in the positive electrode material particles that are not connected to the surface and the interior, they can be regarded as closed pores, and the electrolyte cannot infiltrate the closed pores. Therefore, it is necessary to deliberately control the extension direction of the microcracks to avoid counting the closed pores and causing unstable battery test data. Therefore, controlling the morphology of the above-mentioned microcracks and their content in the positive electrode material particles is beneficial to controlling the gas production behavior of the positive electrode material when used as a pole piece or a secondary battery. Specifically, the present application characterizes the content of the above-mentioned microcracks by the number of positive electrode material particles with microcracks.
[0052] In some embodiments, the gas production of the positive electrode material at 60°C for 7 days is 0.1 mL / g to 1 mL / g. For example, the gas production of the positive electrode material can be 0.1 mL / g, 0.25 mL / g, 0.30 mL / g, 0.40 mL / g, 0.45 mL / g, 0.50 mL / g, 0.55 mL / g, 0.60 mL / g, 0.65 mL / g, 0.85 mL / g, 1 mL / g, or any value within the range formed by any two of the above values. The gas production obtained by using the positive electrode material for a secondary battery (such as a soft pack battery) within the above range indicates that the positive electrode material has a relatively low gas production, especially the gas production caused by the anisotropy of the unit cell and the cracks generated by crushing or rolling during processing of the positive electrode material particles, which is beneficial to improve the cycle stability and safety of the secondary battery.
[0053] In some embodiments, the strain rate of the positive electrode material is 0.035% to 0.13%. For example, the strain rate of the positive electrode material can be 0.035%, 0.040%, 0.046%, 0.051%, 0.054%, 0.062%, 0.075%, 0.081%, 0.094%, 0.103%, 0.13% or any value within the range of any two of the above values. The strain rate of the present application is the change of the lattice unit cell parameter, and its meaning is the change of the microstrain calculated by the unit cell volume, so when the strain rate is within the above range, the change of the lattice unit cell parameter is low, which not only shows that the crystal structure of the positive electrode material itself is more stable, but also can effectively prevent the positive electrode material particles from stress concentration to cracks, which is conducive to improving the cycle stability of the secondary battery obtained.
[0054] In some embodiments, the positive electrode material is a single crystal positive electrode material. Compared with polycrystalline positive electrode crystal materials, single crystal positive electrode materials have better structural stability, longer cycle life, higher safety and better compaction performance. The difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of primary particles. The smallest particle of single crystal positive electrode material is usually a monomer primary particle of micrometer level. Electron backscatter diffraction (EBSD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), etc. can be used to characterize and judge whether the obtained positive electrode product is a single crystal material. For example, in SEM analysis, the shape of single crystal positive electrode material particles is generally regular or irregular polyhedral, and obvious particle agglomeration is rare. In TEM analysis, the crystal plane orientation of single crystal positive electrode materials is similar or the same. For ease of understanding, the single crystal positive electrode material of the present application can be understood as containing single grains with the same orientation. That is, a plurality of primary particles may be included in one crystal grain, and all primary particles in one crystal grain have the same orientation.
[0055] It can be understood that the single grain in the present application can be a single particle composed of one primary particle, or a single particle formed by the agglomeration of multiple primary particles. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. A primary particle refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and a secondary particle refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. Quasi-secondary particles refer to particles formed by the adhesion of several single particles. Generally, the roundness of quasi-secondary particles is lower than that of the above-mentioned conventional secondary particles.
[0056] It should be specifically noted that the single crystal positive electrode materials known to those skilled in the art are not single crystals in the strict sense of crystallography. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strains, and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more "single crystal-like morphology" positive electrode materials, which show large single crystal-like particle sizes in size, as distinguished from polycrystals composed of many small primary particles.
[0057] In some embodiments, the particles include one or more primary particles, all primary particles in at least one particle have the same orientation, and the average particle size of the primary particles is 1 µm to 5 µm. In this way, the positive electrode material can stably achieve its own high filling while reducing the risk of cracking due to extrusion after the particles reach their maximum density. Since the grains have the same orientation, the stress and strain of the positive electrode material particles during the charge and discharge cycle can be alleviated, and the risk of cracking of the positive electrode material particles during the cycle can be reduced, thereby improving the structural stability of the positive electrode material. It should be noted that the grain orientation of the positive electrode material can also be tested by electron backscatter diffraction (EBSD), and 100 single grains with the same orientation are randomly selected, and the particle size of each grain is measured. The arithmetic mean is the average particle size of the above single grains.
[0058] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g to 1 m 2 / g. For example, the specific surface area of the positive electrode material can be 0.5 m 2 / g, 0.6 m 2 / g, 0.66 m 2 / g, 0.72 m 2 / g, 0.78 m 2 / g, 0.8 m 2 / g, 0.9 m 2 / g, 1m 2 / g or any value within the range formed by any two of the above values. Controlling the specific surface area of the positive electrode material within the above range is beneficial to reducing the contact between the electrolyte and the material, reducing the side reaction between the material and the electrolyte, and thus reducing the gas generation behavior of the positive electrode material in the battery.
[0059] In some embodiments, the particle sizes D10, D50 and D90 of the positive electrode material satisfy (D90-D10) / D50 greater than or equal to 1.0. For example, (D90-D10) / D50 can be 1.0, 1.1, 1.15, 1.18, 1.20, 1.22, 1.23, 1.24, 1.30, 1.31 or any value within the range formed by any two of the above values. Among them, the measured volume-based cumulative particle size distribution D10 represents the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D50 represents the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, and D90 represents the particle size corresponding to the cumulative particle size distribution percentage reaching 90%. When the above particle size distribution of the positive electrode material is within the above range, the large particles with larger particle size of the positive electrode material and the small particles with smaller particle size can cooperate with each other, and the small particles fill the pores between the large particles, which is beneficial to improve the tap density and powder compaction density of the positive electrode material.
[0060] In some embodiments, the tap density of the positive electrode material is greater than or equal to 1.8 g / cm 3 For example, the tap density of the cathode material can be 1.8 g / cm 3 , 1.9 g / cm 3 , 2.0 g / cm 3 , 2.1 g / cm 3 , 2.2 g / cm 3 , 2.3 g / cm 3 , 2.4 g / cm 3 Or any value within the range formed by any two of the above values. The above higher tap density is conducive to improving the compactness between the positive electrode material particles, thereby improving the transmission of active particles and the conduction of electrons, increasing the battery energy density, extending the cycle life and improving the safety performance.
[0061] In some embodiments, the powder compaction density of the positive electrode material at 3 T tonnage is greater than or equal to 3.0 g / cm 3 For example, the compacted density of the above powder of the positive electrode material can be 3.0 g / cm 3 、3.1 g / cm 3 , 3.12 g / cm 3 、3.13 g / cm 3 、3.14 g / cm 3 , 3.15 g / cm 3 、3.16 g / cm 3 、3.17 g / cm 3 、3.18 g / cm 3 、3.19 g / cm 3 Or any value within the range formed by any two of the above values. The above-mentioned higher powder compaction density is conducive to reducing the distance between the positive electrode material particles, increasing the contact area, increasing the conductive channels and bridges, and increasing the active area that can participate in the reaction, thereby facilitating the improvement of the specific capacity of the battery.
[0062] In some embodiments, the powder conductivity of the positive electrode material is greater than or equal to 1×10 -4 S / cm. For example, the powder conductivity of the positive electrode material can be 1×10 -4 S / cm, 1.2×10 -4 S / cm, 1.6×10 -4 S / cm, 1.7×10 -4 S / cm, 1.8×10 - 4 S / cm, 1.9×10 -4 S / cm, 2.0×10 -4 S / cm, 2.1×10-4 S / cm, 2.3×10 -4 S / cm or any value within the range formed by any two of the above values. Controlling the powder conductivity of the positive electrode material within the above range is conducive to making the material have a lower impedance, thereby improving the conductivity of the obtained electrode sheet or secondary battery.
[0063] In some embodiments, the unit cell size of the positive electrode material is 80 nm to 110 nm. For example, the unit cell size of the positive electrode material can be 80 nm, 85 nm, 88 nm, 89 nm, 90 nm, 92 nm, 93 nm, 95 nm, 96 nm, 110 nm, or any value within the range formed by any two of the above values. The material having the above unit cell size has a more stable crystal structure, a large unit cell volume, and is easier to deintercalate lithium during the charge and discharge process of the material, and a shorter lithium ion transmission channel. Therefore, controlling the unit cell size of the positive electrode material within the above range is beneficial to improving the capacity of the resulting secondary battery.
[0064] In some embodiments, the cathode material has the general formula Li a Ni b Co c M (1-b-c) O2, wherein 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, b+c≤1, and M includes one or more of Mn, Ti, Zr, Ca, W, Ba, Y, Nb, Mo, La, Sr, and B. Providing the above elements on the surface of the positive electrode material (such as doping the above elements on the surface) is beneficial to improving the structural stability of the positive electrode material, thereby improving the gas generation problem of the positive electrode material under a high voltage environment.
[0065] In other embodiments, the positive electrode material is a core-shell structure, which includes a core and a coating layer, and the coating layer is disposed on at least a portion of the surface of the core. a Ni b Co c M (1-b-c) O2, wherein 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, b+c≤1, M includes one or more of Mn, Ti, Zr, Ca, W, Ba, Y, Nb, Mo, La, Sr, B. The coating layer includes Li x N y O2, wherein 0≤x≤5, and N is one or more of Zr, Ti, Al, W, Nb, La, Mo and Y. Providing a coating layer including the above materials on the surface of the positive electrode material is beneficial to maintaining the interface stability of the positive electrode material, thereby improving the gas generation problem of the material under a high voltage environment.
[0066] The binder in the positive electrode material layer is used to bond the positive electrode material particles to facilitate the formation of a film layer, and can also improve the bonding force between the positive electrode material layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to a binder polymer, such as polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified SBR rubber or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.
[0067] The conductive agent in the positive electrode material layer is used to form a conductive network, provide a channel for electron transmission, and thus improve the conductivity of the positive electrode material. In some embodiments, the conductive agent includes a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. Among them, the carbon-based material is such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black or carbon fiber; the metal-based material is such as metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; the conductive polymer is such as a polyphenylene derivative.
[0068] Negative plate The present application has no special restrictions on the negative electrode sheet 102, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet 102 includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode material layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector, or it can be a partial area of the negative electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.
[0069] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector (such as carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.).
[0070] In the present application, there is no particular limitation on the thickness of the negative electrode current collector, the negative electrode material layer and the negative electrode sheet, as long as the purpose of the present application can be achieved.
[0071] The negative electrode material layer of the present application includes a negative electrode material, and the negative electrode material includes but is not limited to graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOx (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate, lithiated TiO2-Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.
[0072] The negative electrode material layer in the present application also includes a negative electrode binder and a negative electrode conductor, or the negative electrode material layer also includes a negative electrode binder, a negative electrode conductor and a thickener. The present application has no particular restrictions on the types of negative electrode binders and negative electrode conductors, as long as the purpose of the present application can be achieved. For example, the negative electrode binder includes but is not limited to at least one of the binders of the above-mentioned positive electrode material layer, and the negative electrode conductor may include but is not limited to at least one of the conductors of the above-mentioned positive electrode material layer. The present application has no particular restrictions on the type of thickener, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose.
[0073] In some embodiments, the binder includes but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0074] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0075] Isolation film The material and shape of the isolation membrane 103 used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the isolation membrane 103 includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0076] For example, the isolation film 103 may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0077] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic material. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate; the binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer includes a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).
[0078] Electrolytes The electrolyte has the function of conducting active ions between the positive electrode sheet and the negative electrode sheet. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte adopts an electrolyte. In some embodiments, the electrolyte includes one of a lithium salt and an organic solvent, or further includes an additive. The present application has no particular restrictions on lithium salts, organic solvents or additives, which can be any technology disclosed in the prior art as long as the purpose of the present application can be achieved. For example, lithium salts include but are not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl) imide (Li(N(SO2F)2), LiFSI), lithium bis(oxalatoborate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalatoborate (LiBF2(C2O4), LiDFOB). The organic solvent includes, but is not limited to, a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound or a combination thereof. For example, the carbonate compound includes, but is not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or a combination thereof.
[0079] An embodiment of the present application also provides a method for preparing a positive electrode material, comprising: The first step: mixing the positive electrode material precursor, lithium salt and additives, wherein the additives include a transition metal compound with a low melting point, to obtain a mixture, and sintering the mixture once to obtain a sintered product.
[0080] The additive is a transition metal compound with a low melting point. Such oxides help promote the growth of the positive electrode material and close the cracks generated in the positive electrode material during the growth process. During the sintering process of this step, the additive will accelerate the growth of the positive electrode material in the early stage of sintering and help close the cracks in the positive electrode material in the later stage of sintering, thereby controlling the microcrack content in the sintered product and making the sintered product have a certain roundness and dispersibility.
[0081] In some embodiments, the transition metal compound includes one or more of WO3, B2O3, Sr(OH)2, SrCO3, and SrO.
[0082] In some embodiments, the cathode material precursor includes a material precursor, which may be a hydroxide, an oxide, a carbonate, or a phosphate, etc. In some embodiments, the lithium salt includes one or more of lithium hydroxide, lithium carbonate, lithium oxide, and lithium phosphate.
[0083] In some embodiments, the primary sintering is performed in an oxygen atmosphere. In some embodiments, the primary sintering is performed in stages, with a minimum temperature of not less than 500°C and a maximum temperature of not more than 950°C.
[0084] The second step: subjecting the calcined product to air flow pulverization to obtain a pulverized product.
[0085] In some embodiments, the amount of the mill body in the jet milling is 200 g to 600 g.
[0086] In some embodiments, the air pressure of the jet milling is 0.35 MPa to 0.65 MPa.
[0087] In some embodiments, the specific surface area of the pulverized product is less than or equal to 0.8 m 2 / g.
[0088] Step 3: Mix the crushed product with the coating material and perform secondary sintering to obtain the positive electrode material.
[0089] In some embodiments, the coating material includes a metal oxide.
[0090] The preparation method of the positive electrode material has simple procedures and processes, and the combination of the above-mentioned additives and the control of airflow pulverization parameters is conducive to controlling the generation of microcracks in the positive electrode material, thereby helping to control the number of positive electrode materials with microcracks to fall within an expected range, thereby reducing the storage and circulation gas generation behavior of the obtained positive electrode material under high voltage when used as a battery, and improving the stability and safety of the battery.
[0091] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0092] Embodiment 1: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni 0.65 Co 0.1 Mn 0.25(OH)2, 232 g of LiOH·H2O and 1.8 g of WO3 were uniformly mixed to obtain a mixture, and the mixture was placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consisted of three stages at temperatures of 500 ℃, 800 ℃, and 920 ℃, respectively, and was rapidly annealed and cooled at a cooling rate of 8 ℃ / min to obtain a single-sintered product.
[0093] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 200 g (20% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.55 MPa to obtain a pulverized material. The specific surface area of the final pulverized material was 0.6 m 2 / g.
[0094] S3. Mix 100 g of the crushed material with 0.2 g of TiO2, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 550°C to obtain a secondary sintered product.
[0095] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0096] Embodiment 2: A positive electrode material, the preparation method of which comprises: S1, 300 g of Ni 0.75 Co 0.05 Mn 0.2 O, 227 g of Li2CO3 and 1.3 g of B2O3 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consists of three stages. The temperatures are 500°C, 800°C, and 910°C, respectively. The mixture is then rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a single-fired product.
[0097] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 240 g (24% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.65 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.75 m 2 / g.
[0098] S3. Mix 100 g of the crushed material with 0.2 g of Al2O3, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 500°C to obtain a secondary sintered product.
[0099] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0100] Embodiment 3: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni 0.6 Co 0.1 Mn0.3 CO3, 220 g of Li2CO3 and 2.4 g of WO3 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consists of three stages, and the temperatures are 500°C, 800°C, and 940°C, respectively. The mixture is then rapidly annealed and cooled at a cooling rate of 10°C / min to obtain a single-fired product.
[0101] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 350 g (35% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.40 MPa to obtain a pulverized material. The specific surface area of the obtained pulverized material was 0.6 m 2 / g.
[0102] S3. Mix 200 g of the crushed material with 0.3 g of ZrO2, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 700 °C to obtain a secondary sintered product.
[0103] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0104] Embodiment 4: The difference from Example 3 is that in S2, the amount of the mill body in the air flow milling is controlled at 600 g (60% of the upper limit of the mill body), and the specific surface area of the milled material is 0.7 m 2 / g.
[0105] Embodiment 5: The difference from Example 3 is that in S2, the amount of the mill body in the air flow milling is controlled at 200 g (20% of the upper limit of the mill body), and the specific surface area of the milled material is 0.5 m 2 / g.
[0106] Embodiment 6: The difference from Example 3 is that in S2, the air pressure of the air flow milling is controlled at 0.3 Mpa.
[0107] Embodiment 7: The difference from Example 3 is that in S2, the air pressure of the air flow milling is controlled at 0.65 MPa, and the specific surface area of the milled material is 0.8 m 2 / g.
[0108] Embodiment 8: The difference from Example 3 is that in S2, the air pressure of the air flow milling is controlled at 0.50 MPa, and the specific surface area of the milled material is 0.7 m 2 / g.
[0109] Embodiment 9: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni0.9 Co 0.05 Mn 0.05 CO3, 230 g of LiOH and 3.7 g of SrO are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consists of three stages, and the temperatures are 500°C, 600°C, and 820°C, respectively. The mixture is then rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a single-fired product.
[0110] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 300 g (30% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.40 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.8 m 2 / g.
[0111] S3. Mix 400 g of the crushed material with 0.8 g of La2O3, and perform secondary sintering in a compressed air atmosphere furnace at a temperature of 650°C to obtain a secondary sintered product.
[0112] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0113] Embodiment 10: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni 0.8 Co 0.1 Mn 0.1 (OH)2, 230 g of LiOH and 2.8 g of SrO are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for a first sintering. The first sintering consists of three stages, and the temperatures are 500°C, 600°C, and 840°C, respectively. The mixture is then rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a first sintering product.
[0114] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 500 g (50% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.3 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.75 m 2 / g.
[0115] S3. Mix 200 g of the crushed material with 0.6 g of TiO2, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 450°C to obtain a secondary sintered product.
[0116] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0117] Embodiment 11: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni 0.72 Co 0.12 Mn 0.16 O, 240 g of Li2CO3 and 3.1 g of B2O3 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consists of three stages. The temperatures are 500°C, 800°C, and 880°C, respectively. The mixture is rapidly annealed and cooled at a cooling rate of 6°C / min to obtain a single-fired product.
[0118] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 400 g (40% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.55 MPa to obtain a pulverized material. The specific surface area of the obtained pulverized material was 0.7 m 2 / g.
[0119] S3. Mix 200 g of the crushed material with 0.3 g of ZrO2, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 650°C to obtain a secondary sintered product.
[0120] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0121] Embodiment 12: A positive electrode material, the preparation method of which comprises: S1, 300 g of Ni 0.55 Co 0.15 Mn 0.30 O, 141 g of Li2CO3 and 1.6 g of WO3 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for primary sintering. The primary sintering consists of three stages. The temperatures are 500°C, 800°C, and 950°C, respectively. The mixture is then rapidly annealed and cooled at a cooling rate of 10°C / min to obtain a single-fired product.
[0122] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 300 g (30% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.6 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.6 m 2 / g.
[0123] S3. Mix 100 g of the crushed material with 0.2 g of Al2O3, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 550°C to obtain a secondary sintered product.
[0124] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0125] Embodiment 13: A positive electrode material, the preparation method of which comprises: S1, 500 g of Ni 0.65 Co 0.07 Mn 0.23 (OH)2, 220 g of Li2CO3 and 3.5 g of SrCO3 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for a first sintering. The first sintering consists of three stages, and the temperatures are 500°C, 850°C, and 920°C, respectively. It is then rapidly annealed and cooled at a cooling rate of 7°C / min to obtain a first-fired product.
[0126] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 450 g (45% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.45 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.65 m 2 / g.
[0127] S3. Mix 200 g of the crushed material with 0.6 g of Y2O3, and perform secondary sintering in a compressed air atmosphere furnace at a temperature of 700°C to obtain a secondary sintered product.
[0128] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0129] Embodiment 14: A positive electrode material, the preparation method of which comprises: S1, 400 g of Ni 0.7 Co 0.1 Mn 0.2 O, 170 g of Li2CO3 and 2.1 g of Sr(OH)2 are uniformly mixed to obtain a mixture, and the mixture is placed in an oxygen atmosphere furnace for a first sintering, the first sintering comprising three stages, the temperatures being 550°C, 800°C, and 930°C, respectively, and rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a first sintering product.
[0130] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 200 g (20% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.3 MPa to obtain a pulverized material. The specific surface area of the obtained pulverized material was 0.7 m 2 / g.
[0131] S3. Mix 200 g of the crushed material with 0.4 g of Al2O3, and perform secondary sintering in oxygen at a temperature of 650°C to obtain a secondary sintered product.
[0132] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0133] Embodiment 15: A positive electrode material, the preparation method of which comprises: S1, 600 g of Ni 0.67 Co 0.05 Mn 0.28 (OH)2, 285 g of LiOH and 2.1 g of WO3 were uniformly mixed to obtain a mixture, and the mixture was placed in an oxygen atmosphere furnace for a single sintering. The single sintering consisted of three stages, and the temperatures were 500°C, 850°C, and 920°C, respectively. The mixture was then rapidly annealed and cooled at a cooling rate of 8°C / min to obtain a single-sintering product.
[0134] S2. The calcined product was subjected to air flow pulverization. The amount of the grinding body during the air flow pulverization was controlled at 600 g (60% of the upper limit of the grinding body). The air pressure during the air flow pulverization was controlled at 0.65 MPa to obtain a crushed material. The specific surface area of the obtained crushed material was 0.8 m 2 / g.
[0135] S3. Mix 200 g of the crushed material with 0.3 g of ZrO2, and perform secondary sintering in an oxygen atmosphere furnace at a temperature of 700 °C to obtain a secondary sintered product.
[0136] S4. After the calcined product is cooled, it is sieved to obtain the positive electrode material.
[0137] Embodiment 16: The difference from Example 3 is that in S1, the amount of WO3 used is 3.0 g; in S2, the amount of the grinding body in the airflow milling is controlled at 600 g (60% of the upper limit of the grinding body), and the air pressure of the airflow milling is controlled at 0.65 MPa.
[0138] Embodiment 17: The difference from Example 3 is that in S1, the amount of WO3 used is 1.5 g; in S2, the amount of the mill body in the air flow milling is controlled at 200 g (20% of the upper limit of the mill body).
[0139] Embodiment 18: The difference from Example 3 is that in S1, the amount of WO3 used is 5.4 g; in S2, the amount of the grinding body in the airflow milling is controlled at 200 g (20% of the upper limit of the grinding body), and the air pressure of the airflow milling is controlled at 0.30 MPa.
[0140] Comparative Example 1: The difference from Example 1 is that 1.8 g of WO3 is not added to S1.
[0141] Comparative Example 2: The difference from Example 2 is that 1.3 g of B2O3 is not added to S1.
[0142] Comparative Example 3: The difference from Example 3 is that 2.4 g of WO3 is not added to S1.
[0143] Comparative Example 4: The difference from Example 3 is that in S1, 2.4 g of WO3 is not added; in S2, the secondary sintering temperature is 600°C.
[0144] Comparative Example 5: A positive electrode material, the preparation method of which comprises: S1, 200 g of Ni 0.90 Co 0.05 Al 0.05 O, 86 g of LiOH·H2O with a D50 of 10.4 μm are added into a mixing container, and 3 g of H3BO3 and 1.2 g of LiF are added and mixed evenly to obtain a mixture. The mixture is placed in an oxygen atmosphere furnace for a primary sintering. The primary sintering temperature is 550 ℃, the primary sintering time is 6 h, and the heating rate is 5 ℃ / h to obtain a single-fired product.
[0145] S2. After cooling, the calcined product is crushed to obtain crushed material.
[0146] S3. Add 100 g of the crushed material and 14.8 g of Li2CO3 with a D50 of 4.2 μm into a mixing container, and add 1.7 g of niobium pentoxide at the same time, mix evenly to obtain a mixture, and place the mixture in an oxygen atmosphere furnace for secondary sintering. The secondary sintering temperature is 900 °C, the primary sintering time is 8 h, and the heating rate is 5 °C / h to obtain a secondary sintering product.
[0147] S4. After cooling, the calcined product is crushed and sieved to obtain the positive electrode material.
[0148] Comparative Example 6: A positive electrode material, the preparation method of which comprises: S1, 200 g of Ni 0.90 Co 0.08 Al 0.02 O and 73 g of LiOH·H2O with a D50 of 6.5 μm are added into a mixing container, and 2 g of SrCO3 and 1.4 g of NH4F are added and mixed evenly to obtain a mixture. The mixture is placed in an oxygen atmosphere furnace for a primary sintering. The primary sintering temperature is 650 ℃, the primary sintering time is 4 h, and the heating rate is 5 ℃ / h to obtain a single-fired product.
[0149] S2. After cooling, the calcined product is crushed to obtain crushed material.
[0150] S3. Add 100 g of the crushed material and 19.5 g of Li2CO3 with a D50 of 5 μm into a mixing container, and add 3.4 g of niobium pentoxide at the same time, mix evenly to obtain a mixture, and place the mixture in an oxygen atmosphere furnace for secondary sintering. The secondary sintering temperature is 950 °C, the primary sintering time is 10 h, and the heating rate is 5 °C / h to obtain a secondary sintering product.
[0151] S4. After cooling, the calcined product is crushed and sieved to obtain the positive electrode material.
[0152] Examples 1-15 and Comparative Examples 1-6 also provide a positive electrode sheet, the preparation method of which includes: mixing the obtained positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, adding NMP (N-methylpyrrolidone) to form a uniform slurry, coating it on a copper foil, drying it in an oven, and rolling it at a pressure of 10 Mpa, and then cutting it into a circular electrode sheet with a diameter of 14 mm.
[0153] The present application adopts the following method to perform performance tests on the positive electrode materials or positive electrode sheets of Examples 1-15 and Comparative Examples 1-6.
[0154] Test on the proportion of particles with microcracks in positive electrode materials: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and make a pole piece. Use the pole piece as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with microcracks to the total number of positive electrode material particles is counted, and the number of microcracks is characterized by the proportion. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM images obtained from the test can represent the average level of the positive electrode materials tested. Since the pole pieces are not rolled during the production process in this test method, the percentage of microcracks obtained from the test can be regarded as the percentage of microcrack particles in the positive electrode material in powder state.
[0155] Test on the proportion of positive electrode material particles with microcracks in positive electrode sheets: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and roll it under a pressure of 10 Mpa to make a pole sheet. Use the pole sheet as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with microcracks to the total number of positive electrode material particles is counted, and the number of microcracks is characterized by the proportion. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM image obtained from the test can represent the average level of the positive electrode material tested.
[0156] Among them, according to the different causes of their occurrence, the above-mentioned microcracks can be divided into three types: (1) growth microcracks, that is, cracks extending from the surface of the material to the inside of the material during the growth of the positive electrode material particles, or cracks generated inside the particles; (2) crushing microcracks: that is, cracks extending from the surface of the particles to the inside of the material during the crushing process of the positive electrode material particles, or cracks generated inside the particles; (3) post-cycling cracks: After being assembled into button cells, they are cycled, disassembled, and tested by scanning electron microscopy. The cracks observed are mainly caused by intercrystalline displacement.
[0157] Strain rate test of positive electrode materials: The positive electrode materials were tested using an XRD diffractometer with a scanning speed of 1° / min, a step length of 0.005°, and a scanning range of 10° to 70° to obtain the diffraction peaks of the materials. The XRD refinement of the diffraction peaks was then used to calculate and output the strain values of the positive electrode materials. In the XRD refinement process, the calculation of microscopic strain and grain size is one of the key steps. First, according to the Bragg equation and the Scherrer formula, the calculation formula is changed to: By analyzing and , which can be used to describe the degree of FWHM widening caused by strain. In the Rietveld refinement process, the pseudo-Voigt function is used to represent the half-height width (FWHM) of the diffraction peak function. The formula is divided into two parts: Gaussian and Lorentzian, which contain parameters related to microscopic strain and grain size respectively. The specific formula is: Gaussian part: , the Lorentz part: , where U and Y are parameters related to microscopic strain, and X and P are parameters related to grain size, which correspond to the peak shape correction parameters GU, LY, LX and GP in the refinement process. Therefore, the four parameters can be derived by refining the peak shape of the measured XRD data, and then substituted into the corresponding calculation formula to obtain the microstrain parameters.
[0158] Gas production test of positive electrode materials: The positive electrode materials were assembled into 2 Ah soft-pack batteries, stored in a high-temperature oven at 60 °C for 7 days, and the gas production was tested using the drainage method. The obtained gas production is the 7-day gas production of the soft-pack battery per unit mass, in mL / g.
[0159] Specific surface area test of positive electrode material: The specific surface area was tested using an American Micrometer tester, and the test was performed after degassing at 300 °C in vacuum for 1 h.
[0160] Tap density test of positive electrode materials: Dandong Better BT-303 was used to test the tap density of positive electrode materials, with a vibration frequency of 3000 times / min, a vibration time of 1 min, and a vibration amplitude of 3 mm±0.1 mm.
[0161] Powder compaction density test of positive electrode material: The powder compaction density of the positive electrode material is tested using a compaction density meter. Under a pressure of 3 T, the compaction density is the compaction density under 3 T.
[0162] The powder conductivity test method is to test it by the probe method of the powder conductivity instrument under a pressure of 20KN.
[0163] Particle size test of positive electrode material: Malvern laser particle size tester MS 3000 was used to test the particle sizes D10, D50 and D90 of the positive electrode material, and L = (D90-D10) / D50 was calculated.
[0164] Unit cell size test of positive electrode material: The positive electrode material is tested by XRD diffractometer to obtain the peak intensity of 003 and 104 diffraction peaks, calculate I003 / I104, obtain the half-peak width related to 003 and 104, and calculate Dp by Bragg formula.
[0165] Orientation test of primary particles of grains: Equipment: Electron backscatter diffractometer (EBSD) mounted on a scanning electron microscope, model Gemini SEM300. Method: Observing and measuring the color of a single primary particle in a grain can determine whether the grain contains a single grain with all primary particles having the same orientation. When the colors of all primary particles in a grain are the same, it is determined that all primary particles in the grain have the same orientation.
[0166] Secondary battery electrochemical cycle performance test: After the positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry and coated on aluminum foil, dried in an oven, and rolled at a pressure of 10 MPa, and cut into a circular pole piece with a diameter of 14 mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry, the diaphragm is Cellgard diaphragm, the electrolyte is a 1 mol / L LiPF6 solution with EC / PC / DEC as solvent, and the counter electrode is a lithium sheet. The entire assembly process is assembled in a glove box filled with argon, and the oxygen content and moisture content in the glove box are controlled below 0.5 ppm. The test was carried out for 100 cycles at a temperature of 25 ℃±1 ℃, a voltage range of 3.0 V to 4.4 V, an initial charge and discharge current of 0.1 C (20 mAh / g), and a cycle charge and discharge rate of 0.5 C charge / 1 C discharge.
[0167] For the relevant test results of the above test methods, please refer to Figures 4 to 15 and Table 1.
[0168] See also Figure 4 , Figure 5 and Figure 6 Taking Example 1 as an example, after SEM analysis in the above-mentioned test method, taking the observed field of view as an example, the positive electrode material with cracks is shown by the arrows in the figure. On the whole, the crack content mainly caused by grain growth before crushing and rolling and the crack content generated after crushing and rolling are both relatively small.
[0169] See also Figure 7 , Figure 8 and Fig. 9 Taking Example 2 as an example, after SEM analysis in the above-mentioned test method, taking the observed field of view as an example, the positive electrode material with cracks is shown by the arrows in the figure. On the whole, the crack content mainly caused by grain growth before crushing and rolling and the crack content generated after crushing and rolling are both relatively small.
[0170] See also Fig.10 , Fig.11 and Fig.12 Taking Comparative Example 1 as an example and the observed field of view as an example, the positive electrode material having cracks is shown by the arrows in the figure, and the overall crack content is relatively high.
[0171] See also Fig.13 , Fig.14 and Fig.15 Taking Comparative Example 4 as an example and the observed field of view as an example, the overall crack content is relatively high, and more cracks can be observed on a single positive electrode material.
[0172] Table 1. Performance test results of positive electrode materials of Examples 1-18 and Comparative Examples 1-6 of the present application In the positive electrode materials prepared in Examples 1-18 of the present application, the proportion of positive electrode material particles with microcracks is in the range of 1.5% to 13%. When made into pole pieces or secondary batteries and participating in charge and discharge cycles, the positive electrode materials have a stable particle structure, few microcracks, and small structural changes during the cycle. Therefore, the newly added intergranular displacement cracks are relatively small. Such positive electrode materials can have better high-temperature cycle stability, and their gas production is significantly lower and their capacity is higher. This shows that controlling the proportion of positive electrode materials with microcracks in the positive electrode materials within the above range can reduce the gas production behavior of the material in practical applications, thereby helping to improve the storage gas production and circulation gas production problems of the positive electrode materials under high pressure conditions.
[0173] Compared with Examples 1-3, Comparative Examples 1-3 do not add corresponding additives during the preparation process, resulting in a significant increase in the number of microcracks in the positive electrode materials obtained in Comparative Examples 1-3 before rolling (i.e., the growth process) and after rolling, and the number of positive electrode material particles with microcracks exceeds the preset range. Too many microcracks will continuously aggravate the infiltration of the electrolyte into the positive electrode material particles, and even cause the electrolyte to continuously erode from the outside of the material to the inside of the particles, resulting in a large number of side reactions, causing difficult-to-control gas production deterioration and other adverse effects, so that these positive electrode materials have significantly higher gas production and lower capacity when used in batteries, which is not conducive to the cycle stability and safety of secondary batteries.
[0174] On the basis of Comparative Example 3, Comparative Example 4 further reduces the temperature of the primary sintering, resulting in further restriction of the growth of the positive electrode material, resulting in more cracks or holes in the positive electrode material particles during the growth process, and the number of positive electrode material particles with microcracks further increases, and their gas production behavior is also significantly worsened, which is not conducive to the cycle stability and safety of the secondary battery.
[0175] Comparative Examples 5 and 6 both use high-nickel positive electrode materials and therefore have relatively high capacities. However, Comparative Examples 5 and 6 only performed surface treatment (coating and doping) on the materials. In the obtained positive electrode materials, the proportion of positive electrode material particles with microcracks is still relatively high, and the gas production in the battery is still not improved. This indicates that microcracks are intrinsic defects of the positive electrode material particles, and that non-direct intervention in the formation of microcracks such as surface treatment cannot effectively solve the problem of continuous gas production caused by microcracks.
[0176] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a plurality of particles, at least some of the particles have microcracks, the size of the microcracks is 0.5 nm to 30 nm, and the number of the particles with the microcracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material. The test method for the number ratio is: A scanning electron microscope test is performed on the positive electrode material to obtain a scanning electron microscope image. 300 positive electrode material particles are selected from the scanning electron microscope image, and the number of positive electrode material particles having the microcracks is counted to obtain the number ratio.
2. The positive electrode material according to claim 1, characterized in that The number of the particles having the microcracks accounts for 4% to 8% of the total number of particles of the positive electrode material.
3. The positive electrode material according to claim 1, characterized in that The microcracks are located on the surface of the particle and extend toward the interior of the particle, or are located inside the particle and communicate with the surface of the particle.
4. The positive electrode material according to claim 1, characterized in that The gas production of the cathode material at 60° C. over 7 days is 0.1 mL / g to 1 mL / g.
5. The positive electrode material according to claim 1, characterized in that The strain rate of the positive electrode material is 0.035% to 0.13%.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The positive electrode material is a single crystal positive electrode material; (2) The particles include one or more primary particles, all the primary particles in at least one of the particles have the same orientation, and the average particle size of the primary particles is 1 µm to 5 µm.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The specific surface area of the positive electrode material is 0.5 m 2 / g to 1m 2 / g; (2) The particle sizes D10, D50 and D90 of the positive electrode material satisfy (D90-D10) / D50 greater than or equal to 1.0; (3) The tap density of the positive electrode material is greater than or equal to 1.8 g / cm 3 ; (4) The powder compaction density of the positive electrode material at 3 T tonnage is greater than or equal to 3.0 g / cm 3 ; (5) The powder conductivity of the positive electrode material is greater than or equal to 1×10 -4 S / cm; (6) The unit cell size of the positive electrode material is 80nm to 110nm; (7) The general formula of the positive electrode material is Li a Ni b Co c M (1-b-c) O2, wherein 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, b+c≤1, and M includes one or more of Mn, Ti, Zr, Ca, W, Ba, Y, Nb, Mo, La, Sr, and B.
8. The positive electrode material according to claim 1, characterized in that The positive electrode material comprises a core and a coating layer, wherein the coating layer is disposed on at least a portion of the surface of the core, and the coating layer comprises Li x N y O2, wherein 0≤x≤5, and N is one or more of Zr, Ti, Al, W, Nb, La, Mo and Y.
9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, characterized in that: The positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of large single crystal lithium ion battery nickel cobalt lithium manganate cathode material
CN110534733A
Transition metal oxide positive electrode material of single crystal type lithium and preparation method and application thereof
CN112830524A
Cited By
Positive electrode material and preparation method thereof, positive electrode plate, battery and energy storage device
CN121617964A
Positive electrode material, positive electrode pole piece thereof, and secondary battery
WO2026052149A1